Challenges for Women Department Chairs - Laurie J Patterson; Amy Kirschke; Pamela Seaton; Leslie Hossfeld (Academic Chairpersons Conference Proceedings, 2016)
Presenters will discuss issues specific to women in a leadership position, primarily as a department chair and work with participants for ideas on how to succeed as a female administrator.
Keywords: Women Leaders; equity; negotiation; bias